Amity & sorrow [large type] - Riley, Peggy, 1965- (Thorndike Press, 2013)
A mother and two daughters drive for days without sleep until their car crashes in rural Oklahoma. The mother, Amaranth, fears her husband will follow them to the ends of the earth. The girls, Amity and Sorrow, can't imagine the world outside their father's polygamous compound. Rescue comes in the unlikely form of Bradley, a farmer grieving the loss of his wife. At first unwelcoming, Bradley allows his abiding tolerance to get the best of him.